Estudio de la actividad EEG en la banda theta y gamma-baja durante la adquisición y recuperación de información visuoespacial incidental e intencional en voluntarios jóvenes sanos y adultos - Junco Muñoz, Mariana Lizeth (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The question about the participation of the same cerebral structures and similar neural processes in encoding both episodic and incidental information along the life is not actually answered. Ageing process appears to affect earlier the incidental encoding and the deficiencies are qualitatively different for incidental or intentional encoding, in support of differential processing of incidental versus intentional encoding/recall. Methodology. The EEG recorded during the emission of correct responses (recall) in an incidental/intentional visuospatial task in fronto-temporal derivations from young (25-40 years old), and elderly (60-85 years old) healthy volunteers was analyzed. Power and coherence between regions were obtained from 4 seconds EEG samples encompassing the decision (old items correctly recognized and new items correctly rejected) and were compared between groups in four conditions: baseline (open eyes), incidental 1 (small load), incidental 2 (high load) and intentional recovery. Results. Higher power in the theta band (4-8 Hz) and gamma band (30-45 Hz) was observed in the elderly adults in frontal and temporal derivations (Fp1, Fp2, F3, F4, F7, F8, T4, T5 and T6). Left intra-hemispheric, and inter-hemispheric F3-F4, F7-F8 AND T3-T4 coherences were lower for elderly participants in the theta band.

La codificación de información visuoespacial adquirida de forma incidental parece ser más vulnerable al envejecimiento que aquella codificada intencionalmente, las deficiencias son cualitativamente diferentes respecto al número de elementos recordados. Se desconoce sí varían las estructuras cerebrales y procesos neurales implicados en la codificación incidental de información episódica visuoespacial a lo largo de la vida. Metodología. Se comparó la actividad electroencefalográfica de voluntarios sanos jóvenes (25-45 años) y adultos mayores (65-85 años) empleando un montaje monopolar para las derivaciones bilaterales fronto-temporales durante la emisión de respuestas correctas (recuerdo) en dos condiciones de codificación incidental/intencional en una prueba visuoespacial. Se analizaron los elementos correctamente reconocidos, los parámetros de poder y la coherencia durante la toma de decisión; y se compararon intergrupalmente en cuatro condiciones: línea basal ( ojosabiertos), recuerdo-incidental-1 (baja-demanda), recuerdo-incidental-2 (alta-demanda) y recuerdo-intencional. Resultados. Los adultos mayores presentaron mayor potencia en la banda Theta (4-8 Hz) y Gamma (30-45 Hz) en las derivaciones Fp1, Fp2, F3, F4, F7, F8, T4, T5 y T6. La coherencia intra-hemisférica e inter-hemisférica en la banda theta de las derivaciones F3-F4, F7-F8 y T3-T4 fue menor en los adultos mayores.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2017-1137; Memoria visuoespacial; Aprendizaje incidental; Envejecimiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2993